Consumer preferences and segmentation in social commerce for shrimp in Bangladesh: implications for female entrepreneurship - Sharmin, Shanjida; Schipmann-Schwarze, Christin; Amjath-Babu, T.S.; Zander, Katrin (Elsevier, 2026)
Digital technology, and social media in particular, has opened up affordable and accessible business opportunities, especially for women who face cultural and financial barriers in traditionally male-dominated markets in many developing countries. Facebook has emerged as the key platform for "social commerce" in Bangladesh, enabling female entrepreneurs to sell a variety of products, including aquatic products such as shrimp. This study explores the factors shaping consumer preferences and identifies distinct consumer segments in Facebook-based social commerce for shrimp, with particular attention to female entrepreneurs. We conducted an online choice experiment in Bangladesh (N = 869) to examine consumer preferences and applied mixed logit and latent class models to analyze the data. The mixed logit results revealed that reliable reviews and safety indications had a statistically significant positive influence on consumer purchase decisions, whereas the attributes 'frozen', 'ready-to-cook', and price had a statistically significant negative impact. The gender of the seller was not a significant determinant in the model. The latent class analysis revealed a more nuanced picture, identifying four consumer segments with divergent priorities across different attributes. While some consumers value affordability and convenience, others prioritize trust-related attributes such as safety indication and reliable reviews. The largest two consumer groups still prefer male sellers, reflecting enduring cultural traditions. Nevertheless, two smaller consumer groups, accounting for about 31 % of all respondents, expressed a preference for buying from female entrepreneurs. This study provides practical insights for researchers and female entrepreneurs seeking to develop targeted strategies that align with diverse consumer preferences in social commerce for aquatic products.